Revealing the Correlation of the Electrochemical Properties and the Hydration of Inkjet-Printed CdSe/CdS Semiconductor Gels - Miethe, Jan F. (Langmuir, 2020)
[Image: see text] The mobility of charge carriers across a semiconductor-nanoparticle-based 3D network (i.e., a gel) and the interfacial transfer of the charge carriers across the nanoparticle network/electrolyte boundary are elementary processes for applications in the fields of sensing and energy harvesting. The automated manufacturing of electrodes coated with porous networks can be realized by inkjet printing. By simultaneous printing of CdSe/CdS dot-in-rod-shaped nanorods (NRs) and the destabilization reagent, CdSe/CdS gel-network-coated electrodes can be obtained. In this work, the charge carrier mobility of the electrons and the holes within the porous CdSe/CdS nanorod gel network is investigated via photoelectrochemistry. Using linear sweep voltammograms (LSVs) and intensity-modulated photocurrent spectroscopy (IMPS), it is shown that the electron is moving within the tip-to-tip-connected CdSe/CdS NR gel structure, while the holes are trapped in the CdSe seed of the semiconductor heterostructures. Furthermore, the preparation process of gel structures is related to the elementary mechanism of hydration, which can be shown via photoelectrochemical long-term studies.